2014
DOI: 10.1155/2014/148465
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms in Multiple Sclerosis from an In Vivo Study with TBSS

Abstract: Clinically significant depression can impact up to 50% of patients with multiple sclerosis (MS) over a course of their life time, which is associated with an increased morbidity and mortality. In our study, fifteen relapsing-remitting MS (RRMS) patients and 15 age- and gender-matched normal controls were included. Diffusion tensor imaging (DTI) was acquired by employing a single-shot echo planar imaging sequence on a 3.0 T MR scanner and fractional anisotropy (FA) was performed with tract-based spatial statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…In fact, some studies reported an association between depression and higher levels of physical disability [13][14][15][16][17], but this finding was not replicated by other studies [18][19][20]. The occurrence of depression has also been associated with neuronal damage in the frontal and temporal lobes [21,22] and to changes in fractional anisotropy in cortical and subcortical structures [23]. The relevance of psychological factors on the development of depression emerged from several studies exploring coping strategies [24,25], personality traits [13], self-perception and disease perception [4,14,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some studies reported an association between depression and higher levels of physical disability [13][14][15][16][17], but this finding was not replicated by other studies [18][19][20]. The occurrence of depression has also been associated with neuronal damage in the frontal and temporal lobes [21,22] and to changes in fractional anisotropy in cortical and subcortical structures [23]. The relevance of psychological factors on the development of depression emerged from several studies exploring coping strategies [24,25], personality traits [13], self-perception and disease perception [4,14,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors [60,61] were unable to find significant correlations between the EDSS score and depressive scores. Most studies, however, found that MS patients with higher EDSS scores had significantly higher depression scores, while significant positive correlations were found between the EDSS and depression scores [62][63][64][65][66][67][68]. This is important as MS functional disability and especially depression predict physical health and quality of life [69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, depression is a reaction to a progressively disabling disease. Also, active lesions in frontal and limbic areas seem to be correlated with depression [13]. Clearly, further researches are needed to clarify the pathogenesis and to establish a causal link between cerebral damage and psychiatric manifestations.…”
Section: Discussionmentioning
confidence: 99%